On the TiAl phase diagram - Namboodhiri T.K.G. (My University, 2025)
The recent results of Swartzendruber et al. on the α-(α + α2) phase boundary in the TiAl phase diagram are compared with the earlier results of Namboodhiri et al. Both of these modifications suggest a shifting of the α-(α + α2) transition point to lower aluminium concentrations and to higher temperatures than those proposed by Blackburn. The region of short-range order determined by electrical resistivity measurements is also delineated. © 1983.